Conductive Ink with Circular Life Cycle for Printed Electronics. Issue 30 (11th June 2022) - Kwon, Junpyo; DelRe, Christopher; Kang, Philjun; Hall, Aaron; Arnold, Daniel; Jayapurna, Ivan; Ma, Le; Michalek, Matthew; Ritchie, Robert O.; Xu, Ting
Abstract: Electronic waste carries energetic costs and an environmental burden rivaling that of plastic waste due to the rarity and toxicity of the heavy‐metal components. Recyclable conductive composites are introduced for printed circuits formulated with polycaprolactone (PCL), conductive fillers, and enzyme/protectant nanoclusters. Circuits can be printed with flexibility (breaking strain ≈80%) and conductivity (≈2.1 × 10 4 S m −1 ). These composites are degraded at the end of life by immersion in warm water with programmable latency. Approximately 94% of the functional fillers can be recycled and reused with similar device performance. The printed circuits remain functional and degradable after shelf storage for at least 7 months at room temperature and one month of continuous operation under electrical voltage. The present studies provide composite design toward recyclable and easily disposable printed electronics for applications such as wearable electronics, biosensors, and soft robotics. Abstract : The recyclability and sustainability of printed electronics have important design aspects in reducing the costs and environmental burden of electronic waste. Enzymatic degradation can be considered, but resource‐intensive purification of enzymes limits scalability, and their stability is uncertain under electrical voltage and long‐term storage. By employing a customized enzyme protectant, the ink can be disintegrated and recycled in warm water.